PEKERJA PEREMPUAN INDONESIA, POTRET PEKERJA TIDAK DIBAYAR(ANALISIS DATA SAKERNAS 2018) - Opan Fauzan Hamdan (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2019)
AbstractTraditional norms and gender discrimination are still issues that continue to be inherent in most Indonesian women. This is a barrier for them to get high education and decent work. One problem that still occurs is the large number of female workers who are trapped in the status of unpaid workers. Recorded from 50.08 percent of the participation of female workers in Indonesia, there were around 31.49 percent who were unpaid workers (ILO, 2017). This shows that women workers in Indonesia still have not gotten a decent place in the labor market. This study aims to analyze the effect of education level and marital status on the employment status of women (paid or unpaid) with control variables: age, area of residence, number of household members, presence of children aged less than 5 years, and employment sector. The logistic regression results show that women are more likely to be unpaid workers at 11.4 times than men. Women with low education, working in the agricultural sector and living in rural areas have a higher tendency to become unpaid workers.Providing opportunities for women to obtain a higher education can improve their skills and open up wide opportunities to obtain decent work so that in the end it can reduce the gap between men and women especially in employment.